Signs and symbols in traditional art of Kazakhs. - Ivanova A.A.; Lichman E.Y.; Grechneva N.V. (Культурное наследие Сибири, 2020)
Analysis of symbols and signs, forming traditional Kazakh culture is conducted in the article. The authors concludes that specifics of art is in the fact that it attracts different languages of culture into its sphere, selects their semiotic means, and develops their expressive abilities.